Answer: The answer is [tex]21a(2x+3y)(2b-1).[/tex]
Step-by-step explanation: Given expression is as follows
[tex]E=(14x+21y)(6ab-3a).[/tex]
We are to write the above expression "E" as a product of two binomials and a monomial.
A monomial is an expression with a single term and a binomial is an expression with two terms.
So, let us start as follows -
[tex]E\\\\=(14x+21y)(6ab-3a)\\\\=7(2x+3y)3a(2b-1)\\\\=21a(2x+3y)(2b-1).[/tex]
Here,
[tex]21a~\textup{is a monomial and}~(2x+3y),~(2b-1)~\textup{are binomials}.[/tex]
Thus, the required factorisation is
[tex]E=21a(2x+3y)(2b-1).[/tex]